2019
DOI: 10.2147/ijn.s185122
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhanced osteoinduction of electrospun scaffolds with assemblies of hematite nanoparticles as a bioactive interface</p>

Abstract: PurposeElectrospun scaffolds have been studied extensively for their potential use in bone tissue engineering. However, their hydrophobicity and relatively low matrix stiffness constrain their osteoinduction capacities. In the present study, we studied polymer electrospun scaffolds coated with hydrophilic hematite nanoparticles (αFeNPs) constructed using layer-by-layer (LbL) assembly to construct a bioactive interface between the scaffolds and cells, to improve the osteoinduction capacities of the scaffolds.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, the cells on the composite scaffolds (PCL/nHA group, PCL/BNPs group, PCL/NNPs group and PCL/nHA/NNPs group) seemed to show better adherence with increased cell numbers ( Figure 7F ) and better cell-fiber entanglement, perhaps due to the better surface properties with increased hydrophilicity and the presence of the nanoparticles and nHA providing more cell adhesion sites. 39 Nano hydroxyapatite can induce adhesion, proliferation and differentiation of osteoblasts. Zhang et al prepared composite material loaded with nHA as scaffolds for bone regeneration, and found that the composite scaffolds could promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the cells on the composite scaffolds (PCL/nHA group, PCL/BNPs group, PCL/NNPs group and PCL/nHA/NNPs group) seemed to show better adherence with increased cell numbers ( Figure 7F ) and better cell-fiber entanglement, perhaps due to the better surface properties with increased hydrophilicity and the presence of the nanoparticles and nHA providing more cell adhesion sites. 39 Nano hydroxyapatite can induce adhesion, proliferation and differentiation of osteoblasts. Zhang et al prepared composite material loaded with nHA as scaffolds for bone regeneration, and found that the composite scaffolds could promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In another study which focused on bone differentiation, Karimi et al applied Baghdadite nanoparticle-coated with poly l-lactic acid (PLLA) ceramics electrospun scaffold which can improved osteogenic differentiation of adipose tissue-derived mesenchymal stem cells [1]. Also in a study which was done by Ma et al polymer electrospun scaffolds coated with hydrophilic hematite nanoparticles (αFeNPs) constructed to create a bioactive interface between the cells and scaffolds and increase the osteoinduction capacities of the scaffolds [28]. In the present study, the presence of clay and graphene nanoparticles in PAN-based scaffolds were approved with positive effects on uniformity of scaffolds and lead to bone differentiation of AD-MSCs which were seeded on nanofiber scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophilicity of scaffolds is one of the most important parameters in the manufacture of scaffolds to make it possible for cells to adhere to and develop [29]. Via the contact angle test, the hydrophilicity of the scaffold was evaluated [30]. In the PCL, the water touch angle is around 118.4 • ± 2.0 • .…”
Section: Hydrophilicity Testmentioning
confidence: 99%